2018
DOI: 10.18383/j.tom.2018.00051
|View full text |Cite
|
Sign up to set email alerts
|

Multivoxel 1H-MR Spectroscopy Biometrics for Preoprerative Differentiation between Brain Tumors

Abstract: We investigated multivoxel proton magnetic resonance spectroscopy (1H-MRS) biometrics for preoperative differentiation and prognosis of patients with brain metastases (MET), low-grade glioma (LGG) and high-grade glioma (HGG). In total, 33 patients (HGG, 14; LGG, 9; and 10 MET) were included. 1H-MRS imaging (MRSI) data were assessed and neurochemical profiles for metabolites N-acetyl aspartate (NAA) + NAAG(NAA), Cr + PCr(total creatine, tCr), Glu + Gln(Glx), lactate (Lac), myo-inositol(Ins), GPC + PCho(total ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 27 publications
2
18
0
3
Order By: Relevance
“…We found that voxels, that were segmented as FLAIR-intensity, could be differentiated from vasogenic edema and tumor-infiltrating regions according to their metabolic profiles, with the first showing increased intensities of myo-inositol, which is a metabolite known as an “osmolyte” [ 30 ] and the last showing increased intensities of malignancy-related metabolites, such as macromolecules. These results are comparable to other studies conducted for preoperatively classification of brain tumors, in pediatric and adult population [ 6 , 7 , 15 , 16 , 28 , 31 ]. In our study, we analyzed and proved the accuracy with which MRS can discern between a brain lesion and normal brain tissue, which is in line with previous reports in the literature [ 3 , 7 , 24 , 28 , 29 , 31 , 32 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found that voxels, that were segmented as FLAIR-intensity, could be differentiated from vasogenic edema and tumor-infiltrating regions according to their metabolic profiles, with the first showing increased intensities of myo-inositol, which is a metabolite known as an “osmolyte” [ 30 ] and the last showing increased intensities of malignancy-related metabolites, such as macromolecules. These results are comparable to other studies conducted for preoperatively classification of brain tumors, in pediatric and adult population [ 6 , 7 , 15 , 16 , 28 , 31 ]. In our study, we analyzed and proved the accuracy with which MRS can discern between a brain lesion and normal brain tissue, which is in line with previous reports in the literature [ 3 , 7 , 24 , 28 , 29 , 31 , 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…These results are comparable to other studies conducted for preoperatively classification of brain tumors, in pediatric and adult population [ 6 , 7 , 15 , 16 , 28 , 31 ]. In our study, we analyzed and proved the accuracy with which MRS can discern between a brain lesion and normal brain tissue, which is in line with previous reports in the literature [ 3 , 7 , 24 , 28 , 29 , 31 , 32 ]. Moreover, our data supports that MRS is a valid tool that can separate between edema regions with a suppressed intensity (ventricle-like signature) or tumor-infiltrative regions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In low grade glioma, ML is low, whereas in high grade gliomas ML can dominate the spectrum, depending on the level of necrosis. Different types of brain tumors have been discriminated based on the spectrum profile, including MM + ML, and classifiers built for computer‐aided diagnostics 128,129 allowing the prediction of the tumor type and grade. In a study on the relationship between distance to the malignant glioma core and spectral pattern, ML + MM were an important factor for demarcation of the solid brain tumor 130 .…”
Section: Disease Dependence Of MM and Mlmentioning
confidence: 99%
“…The first tendency is to improve the performance of imaging modalities, and the second is to explore the differences among METs from different primary sites. For the first tendency, many imaging modalities have been proposed, including routine MRI and various advanced MRI modalities, such as magnetic resonance spectroscopy, diffusionweighted imaging (DWI), diffusion tensor imaging, diffusion kurtosis imaging, perfusion-weighted imaging (PWI), arterial spin labeling, and amide proton transfer-weighted imaging (Chen et al, 2012;Tan et al, 2015;Salice et al, 2016;Durmo et al, 2018;Holly et al, 2018;Kamimura et al, 2019;Xi et al, 2019). For the second tendency, the relative cerebral blood volume showed no difference among METs from the lungs (MET-lung), breasts, gastrointestinal tract, and skin (Askaner et al, 2019).…”
Section: Introductionmentioning
confidence: 99%